2021
DOI: 10.1021/acsomega.1c04369
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Characteristics of Oil Recovery from Oily Sludge by Sodium Lignosulfonate Treatment

Abstract: The separation of oil components from oily sludge is an important component of soil remediation and energy recovery. Therefore, establishing a green and efficient separation technology is of great significance. In this study, oily sludge was separated using sodium lignosulfonate (SL) treatment. The effects of temperature, SL concentration, rotate speed, time, and pH on the oil removal rate were studied. The optimal conditions were as follows: temperature, 30 °C; SL concentration, 2.0 g·L–1; rotate speed, 200 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The efficiency of oil removal using traditional SL treatment and DL treatment were compared. Traditional SL treatment was performed according to the method reported by Ma et al [ 24 ]. The specific method and process of DL treatment were described by Zhao et al [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of oil removal using traditional SL treatment and DL treatment were compared. Traditional SL treatment was performed according to the method reported by Ma et al [ 24 ]. The specific method and process of DL treatment were described by Zhao et al [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…The separation of OS using SL was investigated in our previous study. The oil removal efficiency was higher by 12.86% compared to using traditional sodium dodecyl sulfonate [ 24 , 25 ]. However, SL is a randomly branched polymer and differs from ordinary surfactants in that it cannot form a regular phase interface state.…”
Section: Introductionmentioning
confidence: 99%
“…Ions, lignin sulfonates, and calcium chloride are the main chemical substitutes [ 14 , 15 ]. Chemical compounds bind soil particles, causing them to solidify inside soil pores, increasing soil strength [ 16 , 17 ] and decreasing permeability [ 18 , 19 ]. Compared with physical methods, chemical methods are generally more expensive and require sophisticated processes that disrupt the acid-base balance of the environment by considerably increasing the alkalinity of the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Oily sludge has become a serious environmental problem in many countries. It is reported that China produces about 3 million tons of oily sludge every year [2]. Due to the large amount of toxic substances such as petroleum hydrocarbons in oily sludge, it is listed as hazardous waste in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the treatment of oily sludge has become an urgent issue. Among the existing oily sludge treatment methods, solvent extraction method has a good application prospect with the advantages of simple operation, high efficiency and short treatment time [2]. However, a large amount of organic solvent needs to be consumed in the extraction process.…”
Section: Introductionmentioning
confidence: 99%